Epidemic Investigation of Diphtheria Outbreak in Banaskantha District, Gujarat - Amiruddin M Kadri; Bhargav B Dave; Bharat R Desai (Medsci Publications, 2019)
Background: Diphtheria is one of the vaccine printable diseases. With launch of successful vaccination program it has shown dramatic reduction in the cases but still sporadic outbreaks are reported. India is the major contributor in global burden of Diphtheria. Methodology: In the northern district of Gujarat, six deaths due to suspected diphtheria was reported. A group of experts as a State Rapid Response Team visited the district. Team interacted with the district health officials, local treating paediatrician and microbiologist, families of cases and deceased and gathered information. Team had also collected detail of the 47 cases from district health authority and analysed the data received. Results: Three cases were found laboratory confirmed diphtheria and rest of the cases were clinically diagnosed by the paediatrician. Cases were reported from 7 blocks out of 14 blocks and they could be linked temporally and geographically. Mean age of the reported diphtheria cases was 7 years. 82.1% of suspected cases of diphtheria was either unvaccinated or their vaccination status was not known. Case fatality rate was reported 17%. Conclusions: Low immunization status with difficult terrain, vaccination hesitancy has resulted into the outbreak of diphtheria. District health team has initiated response as per the national guidelines. But for prevention of the outbreak in future, improvement of vaccination in highrisk groups/areas and effectively using data from surveillance system for early actions should be carried out.